Incidence of Severe Pain in Newly Diagnosed Ambulatory Patients with Stage IV Cancer - Thomas Isaac; Sherri O Stuver; Roger B Davis; Susan Block; Jane C Weeks; Donna L Berry; Saul N Weingart (Pain Research and Management)
BACKGROUND: Pain is common among cancer patients.